Walk the wire - Baldacci, David (New York : Grand Central Publishing, 2020)
Amos Decker, the FBI consultant with a perfect memory, and Alex Jamison FBI. Return to solve a gruesome murder of a young woman named Irene Cramer, in a booming North Dakota oil fracking town. The promise of a second gold rush has attracted an onslaught of newcomers all hoping for a windfall, bringing with them problems, including drugs, property crimes, prostitution and now a grusome murder.
Keywords: Decker, Amos -- (Fictitious character) -- Fiction; United States. -- Federal Bureau of Investigation -- Fiction; Government investigators -- Fiction; Prostitutes -- Fiction; Cults -- United States -- Fiction; Murder -- Investigation -- Fiction; North Dakota -- Fiction; Detective and mystery fiction; Thrillers (Fiction)